Klasifikasi Tinggi Badan Manusia Menggunakan Metode Mask R-CNN - Mulyana, Dadang Iskandar; Adrianto, Sopan; Rasiban; Wahyudi, Ahmad Arif; Sutisna, Sutisna (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The rapid development of the era, of course, becomes a benchmark for an agency to carry out transformation in the field of technology. an agency is expected to be able to implement a system that can provide convenience for many people who are struggling in the field, researchers take the example of a football academic institution. of course the selection to enter the football academic through complicated stages, prospective participants or students must be able to meet various requirements, one of which is height measurement. currently, the selection of height for prospective students is still carried out conventionally by utilizing measuring instruments. this is also the background to this research, in its implementation the researcher used python with the Mask-RCNN method, the conclusion obtained the system is able to detect objects with an accuracy of up to 80%.